2019
DOI: 10.1093/gbe/evz016
|View full text |Cite
|
Sign up to set email alerts
|

Exome Resequencing Reveals Evolutionary History, Genomic Diversity, and Targets of Selection in the ConifersPinus taedaandPinus elliottii

Abstract: Loblolly pine ( Pinus taeda ) and slash pine ( Pinus elliottii ) are ecologically and economically important pine species that dominate many forest ecosystems in the southern United States, but like all conifers, the study of their genetic diversity and demographic history has been hampered by their large genome size. A small number of studies mainly based on candidate-gene sequencing have been reported for P. taeda to date, whereas none are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 75 publications
(110 reference statements)
0
18
0
Order By: Relevance
“…Earlier work has shown that LD decays very rapidly within the P. sylvestris genome ( Dvornyk et al 2002 ; Pyhäjärvi et al 2007 ; Wachowiak et al 2009 ) and also in other conifers such as P. taeda ( Lu et al 2016 ; Acosta et al 2019 ). This study allows for examining longer range patterns of LD than before as in many cases multiple target sequences are positioned within the same scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work has shown that LD decays very rapidly within the P. sylvestris genome ( Dvornyk et al 2002 ; Pyhäjärvi et al 2007 ; Wachowiak et al 2009 ) and also in other conifers such as P. taeda ( Lu et al 2016 ; Acosta et al 2019 ). This study allows for examining longer range patterns of LD than before as in many cases multiple target sequences are positioned within the same scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work has shown that LD decays very rapidly within the P. sylvestris genome (Dvornyk, Sirviö, Mikkonen, & Savolainen, 2002;Tanja Pyhäjärvi et al, 2007;Wachowiak et al, 2009) and also in other conifers such as P. taeda (Acosta et al, 2019;Lu et al, 2016). This study allows for examining longer range patterns of LD than before as in many cases multiple target sequences are positioned within the same scaffold.…”
Section: Linkage Disequilibrium Patterns and Putative Large Inversionmentioning
confidence: 95%
“…These historical clues, based on fossil and pollen records, receive further support from and are complemented by the genomic studies now possible due to recent advancements in next-generation sequencing. For example, Pinus taeda and Pinus elliottii, two species that survived in North American Pleistocene refugia, exhibit different levels of genetic diversity, indicating that P. taeda experienced a drastic bottleneck event probably associated with severe freezing during the late Wisconsin glacial interval (30 000-11 000 yr ago), whereas P. elliottii survived relatively unscathed (Acosta et al, 2019). Picea rubens is another North American species with low genetic diversity as well as poor winter cold tolerance, which probably survived in a warm coastal refugium (DeHayes & Hawley, 1992).…”
Section: Evolution Of Conifer Cold Acclimationmentioning
confidence: 99%